Grandparent-headed families in Australia - Horner, Barbara; Downie, Jill; Hay, David; Wichmann, Helen (Australian Institute of Family Studies, 2007)
Grandparent-headed families are increasingly prevalent in Australia and are one of the fastest growing forms of out-of-home care of children in contact with our public welfare system. However, there is minimal information regarding the characteristics and experiences of Australian grandparent-headed families who assume care through the intervention of child protection services, or those who arrange parental care of their grandchildren privately. Evidence is needed on which to build a policy or service framework to address the health and wellbeing of these grandparents, and ensure quality and safe care of children and young people who are no longer able to live with their biological parents(s).